RANCANG BANGUN APLIKASI THE HAFIZ GUNA MENINGKATKAN HAFALAN AL-QUR’AN BERBASIS MOBILE - Aditia, Muhammad Rizqi; Agitha, Nadiyasari; Anjarwani, Sri Endang (JTIKA (Jurnal Teknik Informatika, Komputer dan Aplikasinya), 2023)
The Quran is a holy book that serves as the foundation for the lives of muslims. Therefore, it is a duty for Muslims to study the Quran and understand its content from an early age. One way that Muslims can understand and practice the content of the Quran is by memorizing it. According to data from the Ministry of Religion of the Republic of Indonesia in 2020, there are 26,973 Islamic boarding schools (pesantren) spread throughout Indonesia. With the increasing number of pesantren in Indonesia, it is expected that many people will become memorizers of the Quran or Hafiz. However, 126 Hafiz face difficulties when memorizing outside of the pesantren environment. This is due to lack of time for review, lack of memorizing partners, and lack of motivation. Based on this problem, the author proposes the idea of developing a mobile application called The Hafiz with Extreme Programming method and the Flutter framework. The application features useful features such as audio of the Quran, a feature for testing memorization. The application has been tested with unit testing, widget testing and received Mean Opinion Score value of 4.56, indicating that The Hafiz application runs well and meets user needs.